Environment vs. economic growth: Do environmental preferences translate into support for Green parties? - Vladimir Otrachshenko; Olga Popova (Global Labor Organization (GLO), 2024)
This paper contributes to a better understanding of the drivers of electoral support for Green parties and the environmental actions they promote, which is key to ensuring the long-term feasibility of environmental policies. We examine whether individual environmental preferences translate into voting for Green parties and analyze the mechanisms behind this effect. Employing an individual-level survey from developed and developing economies matched with the political parties' programs globally, we find that individuals who prefer environmental protection over economic growth are likely to translate their preferences into voting and supporting Green parties. These findings are robust to alternative definitions of Green parties and environmental preferences and to potential endogeneity concerns. The key mechanisms behind this relationship are changes in the stringency of environmental regulations, individual economic and social insecurity, and individual- and country-level exposure to environmental changes. The effect of environmental preferences on Green party voting is less pronounced among individuals living in rural areas and economically disadvantaged individuals, including those with lower education and income. These results suggest that support for Green parties and environmental policies is contingent on voters' economic security even when environmental preferences are strong, emphasizing the need for Green parties to address voters' economic concerns.
Keywords: D72; H11; Q56; Q58; 330; environmental preferences; Green parties; sustainable development; voting